An "in situ templating" strategy towards mesoporous carbon for high-rate supercapacitor and high-adsorption capacity on dye macromolecules. (30th August 2020) - Liu, Kunlin; Wang, Jiuzhou; Yang, Ting; Wang, Hong; Wang, Chengyang; Chen, Mingming
Abstract: Traditional synthesis methods of mesoporous carbon include hard templates (e.g., metal oxides, metal salts and mesoporous silica) and soft templates (e.g., surfactant and block copolymer). However, complicated and time-consuming procedures, high template costs, and harsh preparation conditions hinder the scale-up of these methods. Here, we report a simple and bottom-up strategy to synthesize mesoporous carbon by using the sodium-assisted carbonization of bromobenzene without additional templates added. Depending on the pyrolysis temperature, the obtained material with nanorod structures has a high surface area of 1902 m 2 g −1, a large pore volume of 1.21 cm 3 g −1 and a high degree of graphitization. Meanwhile, the pore-forming mechanism of this strategy is explored and attributed to the " in situ templating" effect of NaBr. The resultant material at 800 °C shows considerable rate performance, long lifetime and high power density. Additionally, the versatility and feasibility of the technique are validated via carbonization of six halogenated aromatic hydrocarbons by three alkali metals. Compared with lithium and potassium, sodium has better pore-forming effect and the obtained products possess a high surface area (1450–2100 m 2 g −1 ) and a large pore volume (1.1–1.6 cm 3 g −1 ). Furthermore, these mesoporous carbons show high adsorption capacity on dye macromolecules. Graphical abstract: Image 1